Tight Sequestration of BH3 Proteins by BCL-xL at Subcellular Membranes Contributes to Apoptotic Resistance - Jessie Pécot; Laurent Maillet; Janic Le Pen; Céline Vuillier; Sophie de Carné Trécesson; Aurélie Fétiveau; Kristopher A. Sarosiek; Florian J. Bock; Frédérique Braun; Anthony Letai; Stephen W.G. Tait; Fabien Gautier; et al. (Cell Reports, 2016)
Anti-apoptotic BCL-2 family members bind to BH3-only proteins and multidomain BAX/BAK to preserve mitochondrial integrity and maintain survival. Whereas inhibition of these interactions is the biological basis of BH3-mimetic anti-cancer therapy, the actual response of membrane-bound protein complexes to these compounds is currently ill-defined. Here, we find that treatment with BH3 mimetics targeting BCL-xL spares subsets of cells with the highest levels of this protein. In intact cells, sequestration of some pro-apoptotic activators (including PUMA and BIM) by full-length BCL-xL is much more resistant to derepression than previously described in cell-free systems. Alterations in the BCL-xL C-terminal anchor that impacts subcellular membrane-targeting and localization dynamics restore sensitivity. Thus, the membrane localization of BCL-xL enforces its control over cell survival and, importantly, limits the pro-apoptotic effects of BH3 mimetics by selectively influencing BCL-xL binding to key pro-apoptotic effectors.